TINJAUAN YURIDIS TERHADAP KASUS PENCURIAN PADA BIDANG OLAHRAGA BERDASARKAN UNDANG UNDANG DI INDONESIA - Pane, Musa Darwin; Octavira, Ferisca Anggia (PERAHU (PENERANGAN HUKUM) : JURNAL ILMU HUKUM, 2025)
This study examines cases of age theft, particularly in the field of sports in Indonesia. The research method uses a normative juridical approach, by analyzing relevant laws and regulations, including laws governing the crime of document or identity forgery. Age theft in early childhood sports in Indonesia is a complex problem that is eliminated due to weak moral awareness, a lack of holistic sports education, and weaknesses in the monitoring and sanction system. To overcome this problem, a multi-faceted approach is needed that involves character education from an early age, increased supervision and strict enforcement of regulations, and improving the quality of sports education in all regions, especially in areas that receive less attention. It is also important to instill the values ​​of sportsmanship and honesty as an integral part of sports culture in Indonesia.